Evaluasi Penyusunan Daftar Pemilih Pada Pemilihan Umum Kepala Daerah di Kabupaten Musi Banyuasin - Yusnan, Yusnan; Idris, Umiyati; Syaparman, Syaparman (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
This study aims to evaluate the preparation of the voter list in the general election of regional heads in Musi Banyuasin Regency. This study uses a qualitative approach which is supported by quantitative data. Search results: 1). Consolidation of voter lists in the regional leadership elections under Musi Banyuasin Regency went well, but in terms of funding or budget, it seems to be very lacking because the existing funds were collected. Copied by KPU RI, transferred to regional management operations19, then for resources Human resources are said to be very scarce, where the moderator only has one person to handle election data continuously for 14 sub-districts. 2). The inhibiting factors for collecting data on the preparation of electoral districts in the general election for the regional head of Musi Banyuasin Regency are: a). For people who do not have a family death certificate, the community data or the number of voters who died without a death certificate will still be recorded in the data to be used as a voter list at the time of the Regional Head election. b). Funeral services that provide data on people who died are still not valid because the data that community members who hold funerals in Musi Banyuasin are not necessarily Musi Banyuasin residents, but the data is still recorded in the congregation. Banyuasin.